Enhancing Exposure and Response Prevention for OCD: A Couple-Based Approach. (March 2013) - Abramowitz, Jonathan S.; Baucom, Donald H.; Wheaton, Michael G.; Boeding, Sara; Fabricant, Laura E.; Paprocki, Christine; Fischer, Melanie S.
The effectiveness of individual therapy by exposure and response prevention (ERP) for obsessive–compulsive disorder (OCD) is well established, yet not all patients respond well, and some show relapse on discontinuation. This article begins by providing an overview of the personal and interpersonal experiences of OCD, focusing on interpersonal processes that maintain OCD symptoms and interfere with ERP. The study then describes a couple-based treatment program that the authors have developed to enhance ERP for individuals with OCD who are in long-term relationships. This program involves psychoeducation, partner-assisted exposure therapy, couple-based interventions aimed at changing maladaptive relationship patterns regarding OCD (i.e., symptom accommodation), and general couple therapy. Three case examples are presented to illustrate the couple-based techniques used in this treatment program.